Identification of Hygiene and Sanitation Knowledge of Pidada Dodol Maker Community in Muara Gembong Bekasi Area - Vivitri Dewi Prasasty; Mario Gunadi; Vinvin Vinvin (MITRA: Jurnal Pemberdayaan Masyarakat, 2018)
Pidada fruit (Sonneratia caseolaris) is a type of fruit from mangrove plants that are used as processed food ingredients into pidada dodol by the coastal community in Muaragembong. The purpose of this community service was to observe the hygiene and sanitation of pidada dodol processing by the people of Biyambong Neighborhood, Mekar Village, Muaragembong Sub-district, Bekasi Regency. Processing pidada dodol is still done traditionally, so it is very important for the community to be aware of the hygiene and sanitation in producing good quality dodol. The expected benefit of this community service activity was to help pidada dodol producers pay attention to the hygiene and safety aspects when making pidada dodol. The results of this community service indicated that the community served understood the importance of hygiene and sanitation during the processing of dodol pidada. Through counseling and the questionnaire on hygiene and sanitation aspects of dodol processing, it is expected that the dodol makers on the coastal of Muaragembong would be more aware of the hygiene and sanitation so that their products become safer and healthier.